1996
DOI: 10.1007/bf01226270
|View full text |Cite
|
Sign up to set email alerts
|

Different expression patterns of cyclins A, D1 and E in human colorectal cancer

Abstract: The expressions of cyclins A, D1 and E at the protein level were investigated by Western blotting in human colorectal carcinomas and in adjacent non-neoplastic colorectal mucosas. Cyclin E was higher in the cancer tissue than in the non-neoplastic mucosa in 92% patients (35 out of 38 cases). However, the cyclin A expression of the mucosa was higher than that of the cancer tissue in 63% (25 out of 40 cases) cases, and only 4 (10%) cancers had higher cyclin A expression. Eleven cancers (27%) demonstrated express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 23 publications
2
40
1
Order By: Relevance
“…This study also supports previous reports of deregulated expression and ampli®cation of cyclin D1 in chemically induced skin tumors (Bianchi et al, 1993;Mitsunaga et al, 1995;Robles and Conti, 1995), human tumors (Bartkova et al, 1995a,b;Wang et al, 1996;Weinstat-Saslow et al, 1995) and in rat mammary tumors (Sgambato et al, 1995). Overexpression of cyclin D1 in the mammary glands of transgenic mice leads to hyperplasia and tumor formation (Wang et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…This study also supports previous reports of deregulated expression and ampli®cation of cyclin D1 in chemically induced skin tumors (Bianchi et al, 1993;Mitsunaga et al, 1995;Robles and Conti, 1995), human tumors (Bartkova et al, 1995a,b;Wang et al, 1996;Weinstat-Saslow et al, 1995) and in rat mammary tumors (Sgambato et al, 1995). Overexpression of cyclin D1 in the mammary glands of transgenic mice leads to hyperplasia and tumor formation (Wang et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…Li et al demonstrated that the three-year survival rate of a cyclin E-negative group was significantly lower than that of the cyclin E-positive group (32). The findings of Wang et al support the theory of overexpression of cyclin E in CRC without a significant correlation with clinical and pathological characteristics (33). Bondi et al did not identify a significant correlation between cyclin E expression and gene amplification in primary colon adenocarcinomas and clinical outcome (34).…”
Section: A B Csupporting
confidence: 54%
“…Overexpression of cD 1 has been reported to negatively influence prognosis in squamous cell carcinomas (SCC) of the larynx (8), but was of no prognostic value in a limited study of NSCLC (16) and mammary carcinomas (17). Increased expression of cE, another key regulatory component of cell cycle control, has been demonstrated in colorectal (18) and mammary carcinomas (19) and has been proposed as a potential and possibly better prognostic marker for breast cancer than cyclin D (19), but its possible role in NSCLC has not been elucidated. Therefore, this study was undertaken to determine the prognostic value of cD 1 and cE in NSCLC.…”
mentioning
confidence: 99%